The pragmatic use of the theory of (despotism) and dualism: (West- democratic) and (East- despotic) in the Western political mind - Ali, Samir Alcheikh (Journal of Economic, Administrative and Legal Sciences, 2021)
The talk about the theory of despotism in Western thought and the duality of (the democratic West) and the east (the despot) comes in a phase that is witnessing violent transformations in the world, with the spread of the Corona epidemic and the fall of many authoritarian regimes in the world, especially after the Arab Spring revolutions of 2010, this coincides with the fall of the West Morally and economically, and being closed in on himself in these crises, after the state of fascination and impotence that afflicted the Asian world before it over two centuries, there is no doubt that the world will change a lot after the Corona crisis, and this crisis may be a tool for the disintegration of Western civilization and the emergence of new Asian powers on the international scene, And the East Asian resurgence, which has been repeatedly described by Western thinkers as despotism and barbarism, through slander and deliberate distortion of facts. This paper tries to stop at these effects of using these categories as a means to forcibly change the world through wars and conflicts, from the universe This theory played pragmatic political roles, by justifying the crimes of the colonial Western wars in the developing world, stealing its treasures, wealth and wealth, and obliterating its cultures, religions and languages. This theory was also used in the twentieth century to justify the American wars in Asia and the Middle East under pragmatic claims to spread freedom and eliminate tyranny.